Rock-salt-type nanoprecipitates lead to high thermoelectric performance in undoped polycrystalline SnSe. Issue 14 (24th January 2017) - Tang, Guodong; Wen, Qiang; Yang, Teng; Cao, Yang; Wei, Wei; Wang, Zhihe; Zhang, Zhidong; Li, Yusheng
Abstract : We report a high ZT value of 1.3 at 850 K for undoped polycrystalline SnSe, and ascribe it to the newly identified cubic Rock-salt nanoprecipitates. Abstract : We report a high ZT value of 1.3 at 850 K for undoped polycrystalline SnSe. The high thermoelectric performance is attributed to a synergistic combination of enhanced power factor and reduction of the lattice thermal conductivity. The presence of rock-salt cubic phase SnSe was identified by X-ray diffraction, transmission electron backscatter diffraction and selected area electron diffraction, which significantly contributes to the enhancement of electrical conductivity and power factor of orthorhombic SnSe material. This new material features a microstructural hierarchy of nanoprecipitates coupled with mesoscale microstructures which leads to a significant reduction of lattice thermal conductivity. As a result, a vast increase in ZT from 0.5 to 1.3 at 850 K was achieved. Our work sheds light on a new mechanism to enhance the thermoelectric properties of SnSe materials.